Analisis Pengaruh PDRB, IPM Dan Tenaga Kerja Terhadap Ketimpangan Distribusi Pendapatan Di Kalimantan Tengah - Devi Astuti; Alexandra Hukom (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
Due to the variation in resources and speed of development between regions at the time it was first implemented, disparities between regions were unavoidable. As a result of uneven economic growth, inequality arises. The purpose of this study was to examine the relationship between the GRDP, HDI, and labor variables on the focus of income in Central Kalimantan. This research methodology uses quantitative methods to study a topic through the use of previously collected data. Income disparity is not significantly affected by the Gross Regional Domestic Product (GRDP) variable and the Human Development Index (IPM) variable. While the labor variable has a significant effect on income inequality. As a result, there has been little or no change in the level of economic tension. This shows that Central Kalimantan has not been able to adequately manage the regional economy.